Implementation of Online-Based Marketing for MSMES in Pasirhandap and Pagerwangi Areas: Implementasi Pemasaran UMKM Berbasis Online di Kawasan Pasirhandap, Pagerwangi - Ubaidilah, Ardian; Nurmahmudah, Lutfiana; Faizal, Muhamad; Ibrahim, Deva; Salsabila, Salsabila; Apriliani, Diah (Institut Riset dan Publikasi Indonesia, 2025)
This community service program was carried out as an effort to empower Micro, Small, and Medium Enterprises (MSMEs) in the Pasirhandap area, Pagerwangi Village, through digital-based marketing assistance. The main problem faced by MSME actors in this area is limited access to digital technology and a lack of understanding of modern promotional strategies. Therefore, this program was designed to provide practical and applicable training, ranging from brand identity creation, utilization of digital platforms such as Shopee and Grab Merchant, to education on the importance of business legality. The program was implemented in three stages: an initial seminar, technical training, and direct mentoring. The results of the activity showed a significant improvement in participants’ understanding and ability to implement digital marketing strategies, as well as increased awareness of the importance of innovation and technological adaptation in the development of small businesses.